Sarawak Economic Development Corporation / Rabiatul ‘Adawiyah Wahab - Wahab, Rabiatul ‘Adawiyah (University Technology MARA Sarawak, 2018)
The Sarawak Economic Development Corporation (SEDC) was established on 1st March 1972 as a state - owned statutory body with the general aim of promoting the commercial, industrial and socio-economic development of the State. SEDC was established under the Perbadanan Pembangunan Ekonomi Sarawak Ordinance (Sarawak Cap. 35), a law duly passed by the Sarawak State Assembly in accordance with the powers conferred on and delegated to the State Government of Sarawak under the Constitution of Malaysia.